2020
DOI: 10.1051/0004-6361/201936846
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic observations of internal gravity waves in the solar atmosphere

Abstract: Aims. We study the properties of internal gravity waves (IGWs) detected in synthetic observations that are obtained from realistic numerical simulation of the solar atmosphere. Methods. We used four different simulations of the solar magneto-convection performed using the CO 5 BOLD code. A magneticfield-free model and three magnetic models were simulated. The latter three models start with an initial vertical, homogeneous field of 10, 50, and 100 G magnetic flux density, representing different regions of the q… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 22 publications
4
20
0
Order By: Relevance
“…The phase difference and coherence spectra of the velocities at two separate layers are then computed from the complex cross-spectrum, 2 (k, ω), where v 1 represents the velocity at layer 1 and likewise for v 2 , and the overbar represents the complex conjugate (see eqns (4-6) of Vigeesh et al [5]). The confidence interval for the phase and coherence measurements and the zero coherence threshold are also computed as described in Vigeesh et al [7]. To study the energy transport by these waves, we estimate the mechanical energy flux spectra by computing the perturbed pressure-velocity ( p − v) co-spectrum represented on the k h -ω dispersion relation diagram.…”
Section: (B) Wave Diagnosticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The phase difference and coherence spectra of the velocities at two separate layers are then computed from the complex cross-spectrum, 2 (k, ω), where v 1 represents the velocity at layer 1 and likewise for v 2 , and the overbar represents the complex conjugate (see eqns (4-6) of Vigeesh et al [5]). The confidence interval for the phase and coherence measurements and the zero coherence threshold are also computed as described in Vigeesh et al [7]. To study the energy transport by these waves, we estimate the mechanical energy flux spectra by computing the perturbed pressure-velocity ( p − v) co-spectrum represented on the k h -ω dispersion relation diagram.…”
Section: (B) Wave Diagnosticsmentioning
confidence: 99%
“…Low-frequency ultraviolet (UV) brightness fluctuations observed in the internetwork region of the low solar chromosphere are believed to be caused by IGWs dissipating in the higher layers [2]. However, the strong effects of magnetic field orientation (attack angle) on the propagation of IGW have been demonstrated by Newington & Cally [3,4] and realistic numerical simulations have shown that the magnetic field present in the solar atmosphere influence the propagation of these waves and likely hinder them from propagating into the upper atmosphere [5][6][7]. At this point, it is still unclear what role the magnetic field plays in the propagation of IGWs into higher layers and how this fits with the brightness fluctuations seen in chromosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the link between brightness fluctuations in internetwork regions and internal gravity waves is not fully resolved. Using three-dimensional simulations of the near-surface obtained with the CO 5 BOLD code [37], Vigeesh et al [38] find that in low layers the magnetic field does not play a significant role in the propagation properties of internal gravity waves. However, the authors find that in higher layers (approx.…”
Section: (C) Gravity Wavesmentioning
confidence: 99%
“…In relatively weak magnetic regions of the lower solar atmosphere, gravity waves with frequencies shorter than 2 mHz (periods 500 s) have been identified in both observations and simulations [3033]. Such waves have been found to have larger energy flux, by approximately one order of magnitude, compared to co-spatial acoustic waves [34], and thus can potentially contribute towards heating of the chromosphere and beyond.…”
Section: Publications In the Special Issuementioning
confidence: 99%
“…IGWs have also been proposed as an agent for the mechanical heating of stellar atmospheres and coronae [10]. More recent studies [11][12][13] show the diagnostic potential of the IGWs for magnetic field in the solar atmosphere at different heights above the solar surface.…”
Section: Introductionmentioning
confidence: 99%